APPLICATION OF LIMITATION PERIOD TO REI VINDICATIO OF IMMOVABLE PROPERTY IN THE REPUBLIC OF ARMENIA (EUROPEAN AND ASIAN LAW REVIEW, 2023)
The present article addresses the issue of applying a three-year limitation period to claims for the recovery possession of immovable property. The problem lies in the fact that the expiration of the short three-year period does not terminate the right of ownership to the property. As a result, when a vindication lawsuit is dismissed due to the expiration of the limitation period, the defendant continues to possess the property unlawfully, leading to dominium sine re. Furthermore, the acquisition of ownership after 10 years of possession due to acquisitive prescription poses difficulties. The acquirer must not only possess the property but also possess it in good faith and as their own, which is practically impossible for the "usurper" of someone else's property, from whom they previously demanded the property as the rightful owner. Thus, a period of uncertainty arises regarding property rights, and the article examines the established practice of Armenian courts concerning mechanisms to circumvent the three-year limitation period. In particular, the extension of the limitation period to the rei vindicatio claim has resulted in its substitution with a negatory claim, leading to a confusion of proprietary remedies. The author also discusses the feasibility of proposed scientific approaches to resolving the raised issue by harmonizing the limitation periods and acquisitive prescription.
Keywords: rei vindicatio; right to ownership; limitation period; immovable property; possession; acquisitive prescription